Unlocking high stability in perovskite solar cells through vacuum-deposited Cs3Bi2I9 thin layer - Shahiduzzaman M.; Hossain M.I.; Gantumur M.; Yue F.; Rafij J.H.; Akhtaruzzaman M.; Nakano M.; Karakawa M.; Tomita K.; Nunzi J.-M.; Taima T. (Elsevier Ltd, 2025)
Perovskite solar cells (PSCs) show great potential for efficient solar energy conversion, but their long-term stability is still a concern. To address this issue, we developed a vacuum-deposited bismuth-based perovskite-like material (Cs3Bi2I9), which forms a high-quality thin film showing remarkable stability over 150 days of air exposure. When combined with a solution-processed MAPbI3 perovskite, the resulting device exhibits improved stability under varying environmental conditions. However, the power conversion efficiency (PCE) drops by 70% compared to the reference MAPbI3-based PSC. An advanced multiphysics optoelectrical device simulation combining 3D FDTD and FEM methods validates these findings, yielding results in excellent agreement with the experimental data. The study also provides insight into the device's optics and electronic properties, revealing the factors that limit its performance. An optimized device design is proposed to reach an 18.81% PCE, higher than the reference device. The findings have significant implications for developing next-generation solar cells, including high-performance tandem solar cells. ? 2024 Elsevier Ltd